1990
DOI: 10.1093/jnci/82.20.1624
|View full text |Cite
|
Sign up to set email alerts
|

Rise in prostatic Cancer Incidence Associated With Increased Use of Transurethral Resection

Abstract: We examined the association between prostatic cancer incidence rates and the rates of transurethral prostatectomy to explore reasons for the nationally reported dramatic increases in incidence rates of prostatic cancer from 1973 through 1986. There was a strong correlation between both incidence of all stages of prostatic cancer combined and of localized disease and the increasing use of transurethral resection, a common surgical procedure usually performed to relieve urinary obstruction due to benign enlargem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(61 citation statements)
references
References 0 publications
0
58
0
3
Order By: Relevance
“…Increases in the incidence before the introduction of PSA testing have been reported in other European countries (Gronberg et al, 1994;Harvei et al, 1996;Moller, 2001) and the USA (Potosky et al, 1990).…”
Section: Discussionmentioning
confidence: 66%
“…Increases in the incidence before the introduction of PSA testing have been reported in other European countries (Gronberg et al, 1994;Harvei et al, 1996;Moller, 2001) and the USA (Potosky et al, 1990).…”
Section: Discussionmentioning
confidence: 66%
“…Prostate cancer is androgen sensitive and it is well confirmed that steroid hormones play a role in carcinogenesis. Secondly, there may be increased detection of existing tumours by transurethral resection (TURP) (Potosky et al,1990;Merrill et al, 1999) and the prostate-specific antigen test (Potosky et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction into routine clinical practice of therapeutic modalities such as TURP and diagnostic procedures such as echo-guided biopsy, transrectal ultrasonography and PSA testing, can be assumed to have made a greater contribution to the incidence increase as a result of an enhanced capability to detect incidental cancers that would otherwise be latent (Potosky et al, 1990;Potosky et al, 1995;Merrill et al, 1999). Thus, incidence may be distorted by the inclusion of varying numbers of so-called latent cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Latent prostate cancer is a common incidental finding at autopsy and prostate surgery (Breslow et al, 1977;Potosky et al, 1990). Small, well-differentiated cancers detected in asymptomatic men are regarded as clinically insignificant (Dugan et al, 1996).…”
Section: Discussionmentioning
confidence: 99%